Re-presentation of Olfactory Exposure Therapy Success Cues during Non-Rapid Eye Movement Sleep did not Increase Therapy Outcome but Increased Sleep Spindles - Rihm, Julia S.; Sollberger, Silja B.; Soravia, Leila M.; Rasch, Björn (Frontiers in Human Neuroscience, 2016)
Exposure therapy induces extinction learning and is an effective treatment for specific phobias. Sleep after learning promotes extinction memory and benefits therapy success. As sleep-dependent memory-enhancing effects are based on memory reactivations during sleep, here we aimed at applying the beneficial effect of sleep on therapy success by cueing memories of subjective therapy success during non-rapid eye movement sleep after in vivo exposure-based group therapy for spider phobia. In addition, oscillatory correlates of re-presentation during sleep (i.e., sleep spindles and slow oscillations) were investigated. After exposure therapy, spider-phobic patients verbalized their subjectively experienced therapy success under presence of a contextual odor. Then, patients napped for 90 min recorded by polysomnography. Half of the sleep group received the odor during sleep while the other half was presented an odorless vehicle as control. A third group served as a wake control group without odor presentation. While exposure therapy significantly reduced spider-phobic symptoms in all subjects, these symptoms could not be further reduced by re-presenting the odor associated with therapy success, probably due to a ceiling effect of the highly effective exposure therapy. However, odor re-exposure during sleep increased left-lateralized frontal slow spindle (11.0–13.0 Hz) and right-lateralized parietal fast spindle (13.0–15.0 Hz) activity, suggesting the possibility of a successful re-presentation of therapy-related memories during sleep. Future studies need to further examine the possibility to enhance therapy success by targeted memory reactivation (TMR) during sleep.